Decrease in Fishery Yields in Response to Hydrological Alterations in the Largest Floodplain Lake (Poyang Lake) in China - Li, Mingzheng; Liu, Chang; Liu, Fei; Wang, Jianwei; Liu, Huanzhang (Frontiers in Earth Science, 2022)
Habitat degradation have cause reduced fishery yields in many freshwater ecosystems, particularly recession of water level in natural lakes. Poyang Lake, the largest freshwater lake and one of the most exploited regions in China, has exhibited a dramatic variation in water level for decades, especially after the operation of the Three Gorges Dam. We evaluate the long-term dynamics of fisheries yields and the relationship to hydrological variability of Poyang Lake from 1990 to 2016. There was a strong positive effect of annual maximum water level (Hmax), minimum water level in April (HMmin4), maximum water level in August (HMmax8), average water level in October (HMmean10) and the number of days water level above the wet threshold (Wetdays) on fisheries yield. All-subsets regression model identified the best variable combination subset which contain eight hydrological variables (R2=0.9493), and the HMmin4, HMmax8 and HMmean10 were the most important variables predictor for fisheries yield (contributing 63.03% of the explained variability). Mann-Kendall test showed that the time series of fisheries yield of the Poyang Lake had significant decreasing trends over the past decades. Moreover, the Wetdays, HMmin4 and HMmean10 also showed significant decreasing abrupt changes, and the abrupt changes time of HMmean10 was the same as fisheries yield in 2005. The mean fisheries yield and HMmean10 dropped from 42581 tonnes and 14.15 m during 1990-2005 to 27464 tonnes and 11.78 m during 2006-2016, respectively. This study is critical for implementing effective strategies for protection of fish resources and lake ecosystems.